1998
DOI: 10.1046/j.1365-2249.1998.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclass distribution of IgA antibodies in saliva and serum after immunization withHaemophilus influenzaetype b conjugate vaccines

Abstract: SUMMARYIgA subclass distribution of antibodies against capsular polysaccharide (PS) of Haemophilus influenzae type b (Hib) was studied in saliva and serum samples of children vaccinated with two (n ¼ 58) or three doses (n ¼ 53) of Hib vaccine. One month after the second dose of Hib conjugate vaccine, at 7 months old, 40% of the children had IgA1 and 41% had IgA2 anti-Hib PS antibodies in saliva. One month after the third dose, at 15-25 months old, IgA1 was the predominating subclass; 72% of the children had Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…However, we found that the changes and the difference in the IgA concentrations were mainly due to changes in the IgA1 concentrations. This is in accordance with our previous findings [11,33]. This suggests that both IgA1 and IgA2 are present, but the vaccine induces IgA1, which, unfortunately, is susceptible to IgA proteases.…”
Section: Discussionsupporting
confidence: 94%
“…However, we found that the changes and the difference in the IgA concentrations were mainly due to changes in the IgA1 concentrations. This is in accordance with our previous findings [11,33]. This suggests that both IgA1 and IgA2 are present, but the vaccine induces IgA1, which, unfortunately, is susceptible to IgA proteases.…”
Section: Discussionsupporting
confidence: 94%
“…80 The IgA2 subclass of IgA antibodies may provide some functional advantage in specific mucosal immune responses over IgA1 as a result of structural differences that make IgA2 relatively resistant to IgA1 protease activity. 81 82 Haemophilus influenzae type b, S pneumoniae, and N meningitidis can produce IgA1 protease, which can cleave IgA1 to Fab and Fc fragments, and can therefore eliminate the Fc mediated functions of IgA1, 82 83 although human secretory IgA has been shown to be resistant to this protease activity.…”
Section: Mechanisms Of Mucosal Immunity Induced By Parenteral Vaccinamentioning
confidence: 99%
“…Saliva samples of children vaccinated with a protein-PS-conjugate vaccine against S. pneumoniae or Hib have been analysed for specific anti-PS IgA antibodies in several studies [10,[40][41][42][43]. Relatively high proportions of anti-PS antibodies detected in saliva of the 7-month-old children after the primary-series vaccination have been of IgA2 subclass, followed by IgA1 dominance after the booster dose [10,40]. The potential effect of IgA1 proteases should be taken into account when testing mucosal vaccines that induce high concentrations of local IgA.…”
Section: Discussionmentioning
confidence: 99%